Pengaruh Kepedulian Orang Tua terhadap Perilaku Belajar Siswa di Kelas - Harningsih Fitri Situmorang (Departement of Mathematics Education, 2023)
The research objective was to determine the influence of parental concern for children on the learning behavior of Class XII students at Simpang Kanan State Senior High School, Bagan Batu. The research population was all Class XII students at SMA Negeri 1 Simpang Kanan, Bagan Batu, namely 249 students, while the sample size was 161 students. Data analysis tools used are multiple regression analysis, correlation coefficient of determination, and hypothesis testing t. The results of the regression equation obtained Ŷ = 12.782 + 0.958X, meaning that the value of the regression coefficient for parental concern (X) is positive meaning that each increase in the parental concern variable has an influence on increasing student learning behavior (Y) in SMA Negeri 1 Simpang Kanan students , Rock Chart. The results of the correlation analysis obtained the value of r = 0.682, meaning that the relationship between parental concern and student learning behavior at SMA Negeri 1, Bagan Batu is quite strong. While the results of the Coefficient of deterrence (2 r) = 46.2%, this means that the variable parental concern influences changes in student learning behavior at SMA Negeri 1 Simpang Kanan, Bagan Batu by 46.2%. The results of the hypothesis test with the t test obtained the value of tcount = 11.768 and the value of ttable = 1.658, because tcount > ttable then H0 is rejected while Ha is accepted, which means that parental concern has a positive influence on student learning behavior at SMA Negeri 1 Simpang Kanan, Bagan Batu .